2022
DOI: 10.1111/cup.14327
|View full text |Cite
|
Sign up to set email alerts
|

The diverse landscape of dermatologic toxicities of non‐immune checkpoint inhibitor monoclonal antibody‐based cancer therapy

Abstract: Background Since their first approval 25 years ago, monoclonal antibodies (mAbs) have become important targeted cancer therapeutics. However, dermatologic toxicities associated with non−immune checkpoint inhibitor (non‐ICI) mAbs may complicate the course of cancer treatment. Data on the incidence and types of these reactions are limited. Methods A comprehensive review was conducted on dermatologic toxicities associated with different classes of non‐ICI mAbs approved for treatment of solid tumors and hematologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 368 publications
0
3
0
Order By: Relevance
“…Although the inflammation of AK from immune checkpoint inhibitors has not been specifically reported, they can potentially lead to such manifestations through diversification of T-lymphocyte and B-lymphocyte populations and subsequent skin damage mediated by inflammatory cytokines and autoantibodies 11. Non-immune checkpoint inhibitor monoclonal antibody-based cancer therapies can also lead to inflamed AK by coexpression of their targets on keratinocytes 12. The dysregulation of the epidermal growth factor receptor and vascular endothelial growth factor receptor pathway in AK may explain the inflammation from panitumumab, erlotinib and sorafenib 13–16.…”
Section: Discussionmentioning
confidence: 99%
“…Although the inflammation of AK from immune checkpoint inhibitors has not been specifically reported, they can potentially lead to such manifestations through diversification of T-lymphocyte and B-lymphocyte populations and subsequent skin damage mediated by inflammatory cytokines and autoantibodies 11. Non-immune checkpoint inhibitor monoclonal antibody-based cancer therapies can also lead to inflamed AK by coexpression of their targets on keratinocytes 12. The dysregulation of the epidermal growth factor receptor and vascular endothelial growth factor receptor pathway in AK may explain the inflammation from panitumumab, erlotinib and sorafenib 13–16.…”
Section: Discussionmentioning
confidence: 99%
“…1 They occur in fewer than 1% of patients treated with targeted inhibitors of BRAF and other small-molecular inhibitors. 1,2 Bullous pemphigoid (BP)-irAE is the most commonly reported autoimmune blistering process among cancer patients treated with anti-programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) and anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) therapies. 3,4 A review of 58 cases of BP-irAE associated with anti-PD-1/PD-L1 immunotherapy demonstrated a median latency of $28 weeks and most often clinical presentation as an eczematous or urticarial lesion or blisters (80%) with a histopathologic pattern of subepidermal bullae (71%) and eosinophils (81%).…”
Section: Introductionmentioning
confidence: 99%
“…Immunobullous skin eruptions constitute a small but significant proportion of immune‐related adverse events (irAEs) to anticancer therapies 1 . They occur in fewer than 1% of patients treated with targeted inhibitors of BRAF and other small‐molecular inhibitors 1,2 . Bullous pemphigoid (BP)‐irAE is the most commonly reported autoimmune blistering process among cancer patients treated with anti‐programmed cell death protein 1 (PD‐1)/programmed death‐ligand 1 (PD‐L1) and anti‐cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) therapies 3,4 .…”
Section: Introductionmentioning
confidence: 99%